2006
DOI: 10.1038/sj.onc.1209487
|View full text |Cite|
|
Sign up to set email alerts
|

hTERT: a novel endogenous inhibitor of the mitochondrial cell death pathway

Abstract: hTERT is the catalytic subunit of the telomerase and is hence required for telomerase maintenance activity and cancer cell immortalization. Here, we show that acute hTERT depletion has no adverse effects on the viability or proliferation of cervical and colon carcinoma cell lines, as evaluated within 72 h after transfection with hTERTspecific small interfering RNAs (siRNAs). Within the same time frame, hTERT depletion facilitated the induction of apoptotic cell death by cisplatin, etoposide, mitomycin C and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
132
2
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(144 citation statements)
references
References 58 publications
9
132
2
1
Order By: Relevance
“…The bars in a-c represent standard errors with ** and *** indicating Pr0.01 and Pr0.001, respectively cell death induced by mitomycin C, a potent DNA crosslinker used in cancer treatment to induce mitochondrial apoptosis. 20,21 Figure 1b shows that DN-Aven 180-362 and the bona fide apoptosis inhibitor Bcl-x L both significantly inhibited apoptosis caused by mitomycin C at different concentrations, whereas expression of full-length Aven did not confer protection under this experimental paradigm.…”
Section: Resultsmentioning
confidence: 99%
“…The bars in a-c represent standard errors with ** and *** indicating Pr0.01 and Pr0.001, respectively cell death induced by mitomycin C, a potent DNA crosslinker used in cancer treatment to induce mitochondrial apoptosis. 20,21 Figure 1b shows that DN-Aven 180-362 and the bona fide apoptosis inhibitor Bcl-x L both significantly inhibited apoptosis caused by mitomycin C at different concentrations, whereas expression of full-length Aven did not confer protection under this experimental paradigm.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it has been shown that overexpression of hTERT suppresses apoptosis at a premitochondrial step before the release of cytochrome c and apoptosis-inducing factor [32]. Recent studies showed that down-regulation of hTERT expression by hTERT specific interfering RNA (siRNA) sensitizes mitochondrial pathways of apoptosis without apparent involvement of telomere erosion due to telomerase inhibition, rather by post-translational activation of Bax protein which triggers a CD-90 independent mitochondrial pathway of apoptosis [33]. More recent report indicated that TERT promotes cellular and organismal survival independent of telomerase activity [34].…”
Section: Telomerase In Apoptosismentioning
confidence: 99%
“…It is unlikely that rapid telomere shortening occurred in that cells, and high dose of TELIN may invoke another physiological response of MOLT-4 cells. hTERT is reported to function in mitochondria to suppress the course of apoptosis process, and so is expected as anticancer target (Massard et al 2006), and we have not excluded the possibility that TELIN potentially targets hTERT in mitochondoria.…”
Section: Suppression Of Telomerase Enzyme By Telinmentioning
confidence: 99%